Research Trends of Local Wisdom in Science Education: A Bibliometric Analysis Based on the Scopus Database - Surya Haryandi; Misbah Misbah; Noor Izzati Pratiwi; Muhdi Harto; Qamariah Qamariah; Ismail Ismail; Erwina Oktavianty (Journal of Mathematics Science and Computer Education, 2026)
This study aims to map the research trends of local wisdom in science education through a bibliometric analysis based on Scopus data. The dataset was obtained from the Scopus export file analyzed in this study and includes 85 documents spanning the 2013–2025 period. Analyses were performed on the annual number of publications, the most productive affiliations, countries of origin, publication sources, the most influential authors based on citations, the most productive authors based on the number of documents, and keyword clusters. The results indicate that research on local wisdom in science education shows an upward trend, particularly after 2019, reaching temporary peaks in 2024 and 2025. Indonesia is highly dominant with 81 documents, while the most productive affiliation is Universitas Negeri Yogyakarta. The most prominent publication source is the Journal of Physics: Conference Series. Based on citations, Parmin is the most influential author with 66 citations, whereas Wilujeng, I. is the most productive author with 3 documents. Keyword mapping reveals that local wisdom serves as the core node connected to science education, science literacy, ethnoscience, sustainability, e-module, augmented reality, and PBL. The primary insight from these findings is that local wisdom is no longer merely positioned as a cultural context in science education; instead, it has evolved into a conceptual foundation for developing scientific literacy, pedagogical innovation, and learning that is relevant to the challenges of sustainable education. These findings confirm that research on local wisdom in science education is evolving from a contextual-cultural orientation toward strengthening scientific literacy, developing instructional materials, and creating innovative technology-based learning. The novelty of this study lies in its bibliometric mapping, which specifically integrates the dimensions of publication productivity, research actors, publication sources, citation impact, and keyword thematic structures into a single comprehensive landscape regarding Scopus-based local wisdom research in science education for the 2013–2026 period. This study contributes to identifying the research landscape, key actors, and potential future research agendas within the field of local wisdom-based science education.